The Relationship Between Diet Patterns And The Incidence Of Anemia In Pregnant Women At Datuk Bandar Community Health Center - Zai, Delviani; Simarmata, Mesrida (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Introduction : Anemia is very dangerous in pregnancy because it can affect the mother and baby. The mother can experience poor body conditions because the blood does not carry enough oxygen and nutrients so that the body is inadequate in getting oxygen and nutrients . Objective : To analyze the Relationship between Pregnant Women's Eating Patterns in the Third Trimester and the incidence of anemia at the Datuk Bandar Health Center . Method: observational research to see if there is a relationship between diet and the incidence of anemia in pregnant women at the Datuk Bandar Health Center. Population and Sample: all pregnant women in the third trimester at the Datuk Bandar Health Center as many as 35 people with the total population sampling technique, the number of samples was 35 people. Place and time: At the Datuk Bandar Health Center, Datuk Bandar District, Tanjung Balai City, North Sumatra Province in February-April 2024. Results : Respondents with poor diet patterns were mostly anemic, 12 people (34%), while respondents with poor diet patterns were mostly not anemic, 20 people (57%). After the chi square test was carried out , the results showed that the p value was 0.000 , so there was a relationship between the respondents' diet patterns and the incidence of anemia in respondents at the Datuk Bandar Health Center, Datuk Bandar District, Tanjung Balai City, North Sumatra Province in 2024. Conclusion : There is a relationship between diet patterns and the incidence of anemia in pregnant women in the third trimester at the Datuk Bandar Health Center in 2024